Violência contra as mulheres no contexto da pandemia : rompendo o silêncio - Concatto, Cristina Schimitt (2023)
This dissertation aims to understand the social experiences of women who have suffered domestic and intra-family violence assisted by the Specialized Reference Center for Social Welfare – CREAS in the municipality of Gramado/RS, during the period of the Covid-19 pandemic, to contribute with subsidies for the qualification of the protection network services. It was decided to delimit the period of the research between March 2020 and March 2021. This study is of paramount importance when faced with the statistics that, despite the fact that the number of domestic violence police reports have decreased, complaints in other channels have increased, such as in Dial 100 and Dial 180. Studies show that isolation with the aggressor made it difficult for women to report violence. The city of Gramado was chosen because the author lives and works in that city; and the choice for the theme arose because the author worked at the Reference Center for Assistance to Women – CRAM for two years. In addition, as academic relevance, the data show that, although Gramado is smaller than the capital of Rio Grande do Sul (RS), its statistics on violence against women are similar to Porto Alegre, considering the number of residents. As specific objectives, we sought to know the social profile of women who suffered domestic and intrafamily violence; analyze which protection network services were accessed by women and their perception of this access; know the route taken by women in the search to cope with the violence experienced until they were assisted by CREAS; and the conjunctural determinants that aggravate the situation of domestic violence during the pandemic. As for the research method, qualitative research with quantifiable data was defined. Data collection included four face-to-face, individual and semi-structured interviews, using a form filled out with the women who agreed to participate. For the analysis of the data obtained, content analysis by Roque Moraes was used, in an analysis with a dialectical-critical approach, revealing the categories historicity, totality, contradiction and mediation. Also, it included the analysis of quantitative data from the records of 22 women who were assisted by CREAS during the research period, as well as the documental analysis of policies and services that aim to face violence against women. Simple descriptive statistics were used in this step for data processing. As research results, reports of institutional violence experienced by the four interviewees stand out: practiced by the civil police station, the Tutelary Council, and the Judiciary. The narratives also reveal that shame and fear constitute factors that prevent the complaint. The four women realized that the Covid-19 pandemic and isolation were factors that increased the violence they suffered, as well as the positive and negative aspects of the service network in coping with violence. And finally, the research identified the need for propositions of social public policies to face violence against women that support the much needed emancipation process.